The effects of the TPRS Method on the Studentsâ€™ English Vocabulary Acquisition - Pinos-Ortiz, Mónica A.; Orbe-Guaraca, Mariory P. (Dominio de las Ciencias, 2018)
The present study investigates the effects the method of teaching language through reading and storytelling (TPRS) in the acquisition of English vocabulary has in second level students in the Catholic University of Cuenca, extension Cañar; and the perceptions that students have when they are taught through this method. The teaching of language through reading and storytelling is a method that uses different resources for language teaching, providing comprehensible input information in imaginary or real situations derived from students' social context and their cognitive and affective needs. 56 students of the second level of the aforementioned university were randomly selected. A group of 30 students formed the experimental group and 26 students the control group. The data was obtained through the Cambridge vocabulary test in the pre and post-test phases to establish the difference between the groups. Additionally, a survey was applied to the students of the intervention group to know their perspectives on the method. The independent t-statistic test was used for the data analysis. The results show that the students of the treatment group obtained better results than the students in the control group in the measures of vocabulary acquisition. Additionally, the results of the survey showed that the students perceive that the strategies derived from the method were of great support to acquire vocabulary in English.